Perbedaan Disfungsi Ereksi pada Pasien Diabetes Melitus Tipe 2 dengan Hipertensi dan Nonhipertensi di RSUD Dr. Moewardi - Rusjaya, I Kadek; Sugiarto, .; Iryawan, Andri (Nexus Kedokteran Klinik, 2014)
Background: Type 2 Diabetes Mellitus is a global and Indonesian health problem which is estimated to increase in the future. One of the long-term complications of diabetes mellitus is the presence of neuropathy which will cause erectile dysfunction. Hypertension often accompanies the presence of diabetes mellitus. Untreated hypertension in diabetes mellitus will worsen the incidence of erectile dysfunction. This happened because in hypertension occurs a vascular endothelial damage and decreased production of NO which is a major mediator of erection. Methods: This study was an observational analytic study with cross sectional approach held in August â September 2014 in the Polyclinic of Internal Medicine RSUD Dr. Moewardi. Sampling was done by Purposive Random Sampling technique, selection was done by checking the inclusion and exclusion criteria of the study sample. The number of samples in this study were 30 patients. Hereafter, the data obtained were statistically analyzed by Chi-Square test (X2). Results: The results of the Chi-Square testâs analysis of the incidence of erectile dysfunction was obtained a significant differences between patients with type 2 diabetes mellitus with hypertension and non-hypertension (p<0,05). Hypertension in diabetes mellitus increases the risk of erectile dysfunction by 9 times compared to non-hypertension (OR=9,750,p=0,008). Conclusions: There was a statistically significant difference of erectile dysfunction between patients with type 2 diabetes mellitus with hypertension and non-hypertension. Hypertension in diabetes mellitus increases the risk of erectile dysfunction by 9,7 times compared to non-hypertension. Keywords: Diabetes Mellitus, Erectile Dysfunction, Hypertension Â